Prognostic value of TIGIT in East Asian patients with solid cancers: A systematic review, meta-analysis and pancancer analysis - Li, Sicong; Li, Lanxing; Pan, Tianyan; Li, Xiaoqun; Tong, Yujia; Jin, Yongdong (Frontiers in Immunology, 2022)
Background: T cell immunoreceptor with Ig and ITIM domains (TIGIT) participates in tumor immune escape by delivering inhibitory signals to T cells. The purpose of this article is to assess the prognostic value of TIGIT and its immunological function in solid cancers. Methods: 3 databases were searched for relevant articles. The main endpoints were overall survival (OS), progression-free survival (PFS), recurrence-free survival (RFS), and disease-free survival(DFS). Hazard ratios (HR) were pooled by using fixed-effects or random-effects models. Pan-cancer analysis of TIGIT were performed based on public online databases, mainly including the Cancer Genome Atlas (TCGA), Genotype-Tissue Expression (GTEx), UCSC Xena. The possible relationships between TIGIT expression and tumor microenvironment (TME), infiltration of immune cells, immune-related genes, tumor mutation burden (TMB), and microsatellite instability (MSI) were revealed in this article. Results: 16 studies met the inclusion criteria. The high expression of TIGIT was associated with worse OS [HR= 1.73, 95% confidence interval (CI) 1.50, 1.99], PFS (HR = 1.53, 95% CI [1.25, 1.88]), RFS (HR = 2.40, 95% CI [1.97, 2.93]), DFS (HR= 6.57, 95% CI [0.73, 59.16]). TIGIT expression was positively correlated with immune infiltration scores and infiltration of CD8 T lymphocytes in all of the cancers included. TIGIT was found to be co-expressed with the genes encoding immunostimulators, immunoinhibitors, chemokines, chemokine receptors, and major histocompatibility complex (MHC), especially in gastroesophageal cancer. TMB and MSI were also associated with TIGIT up-regulation in diverse kinds of cancers. Conclusion: High expression of TIGIT is associated with poorer prognosis in patients with solid cancers. TIGIT is a novel prognostic biomarker and immunotherapeutic target for various solid cancers because of its activity in cancer immunity and tumorigenesis.